The dark tower [videorecording (Blu-Ray)] - Elba, Idris; McConaughey, Matthew, 1969-; Taylor, Tom, 2001-; Kim, Claudia, 1985-; Kranz, Fran, 1983-; Abbey Lee, 1987-; Haley, Jackie Earle, 1961-; King, Stephen, 1947- (Columbia Pictures Industries, 2017)
Based on the best-selling book series by highly-acclaimed author Stephen King. The last Gunslinger, Roland has been locked in an eternal battle with the Man in Black, determined to prevent him from toppling the Dark Tower, which holds the universe together. With the fate of the worlds at stake, good and evil will collide in the epic battle as only Roland can defend the Tower from the Man in Black.--From container.